OPPRESSION AGAINST THE POOR IN JOHN ALEXANDER'S SENSE AND SENSIBILITY (2008): A MARXIST CRITICISM - SARIE, NILA (2011)
The major problem of this study is to reveal how oppression against the poor are reflected in John Alexander's Sense and Sensibility. The objective of this study is to analyze the movie based on its structural elements and a Marxist approach. In analysis, the writer uses qualitative method. The object of the study is John Alexander's Sense and Sensibility released in 2008 in United Kingdom. The data sources consist of primary and secondary data sources. The primary data source is Sense and Sensibility movie itself and the secondary data sources are the other sources related to the primary data such as the information about the director's biography, websites, and the historical background of England in the early of twenty first century. The methods of the data collection are watching the movie, taking notes the important data, arranging the data based on category of elements of literature review , and the last is looking for the supporting data. The technique of data analysis is descriptive analysis. The outcome of the study shows in the following conclusion. First, based on the structural analysis, it is evident that in this movie, the director conveys a message that the poor have the right to fight against the injustice, particularly committed by the rich. Second, this movie portrays the social reality of England that the poor experiences oppression. This movie illustrates that the oppression toward the poor has lasted for a very long time since the time of Jane Austen. In this movie, Alexander criticizes that despite the progress, England was not quite successful in dealing with the disparity between the rich and the poor.